A comparison of pulse oximetry and cerebral oxygenation in children with severe sleep apnea–hypopnea syndrome: a pilot study. (31st May 2017) - Olmo Arroyo, Jorge; Khirani, Sonia; Amaddeo, Alessandro; Griffon, Lucie; De Sanctis, Livio; Pouard, Philippe; Fauroux, Brigitte
Summary: Near infrared spectroscopy (NIRS) has been used to assess the impact of obstructive sleep apnea–hypopnea syndrome (OSAHS) on cerebral oxygenation. However, the relationship between the variations in the cerebral tissue oxygen saturation (ΔTOI) and pulse oximetry (ΔSpO2 ) has not been assessed in children with OSAHS. Consecutive clinically stable children with severe OSAHS [apnea–hypopnea index (AHI) >15 events h −1 ] diagnosed during a night‐time polygraphy with simultaneous recording of cerebral oxygenation with NIRS (NIRO‐200NX, Hamamatsu Photonics KK) were included between September 2015 and June 2016. Maximal ΔSpO2 (SpO2 drop from the value preceding desaturation to nadir) and concomitant variations in transcutaneous carbon dioxide (ΔPtcCO2 ), maximal ΔTOI and maximal variations in cerebral oxygenated (O2 Hb) and deoxygenated (HHb) haemoglobin were reported. The relationships between ΔSpO2, ΔPtcCO2 and ΔTOI, ΔO2 Hb and ΔHHb were investigated. The data from five children (three boys, aged 9.6 ± 6.7 years, AHI 16–91 events h −1 ) were analysed. Strong correlations were found between ΔSpO2 and ΔTOI ( r  = 0.887, P  < 0.001), but also with ΔO2 Hb and ΔHHb with a particular pattern in the youngest child with a dark skin pigmentation. Mean ΔSpO2 was 20 ± 17% and mean ΔTOI was 8 ± 7%. Maximal ΔSpO2 of approximately 70% were coupled with ΔTOI of no more than 35%. ΔPtcCO2 correlated only weakly with the cerebral oxygenation indexes. This pilot study shows a strong relationship between pulse oximetry and cerebral oxygenation in children with OSAHS, with lower changes in TOI compared to SpO2 . Future studies should address the clinical impact of respiratory events on cerebral oxygenation and its consequences.